2020
DOI: 10.29333/ejgm/8212
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Effects of Mobility Trends on the Statistical Models of the COVID-19 Virus Spreading

Abstract: The history of the Pandemics makes a significant impact on the memory and behavior of the affected communities. It is important to study the connection between human mobility and the spread of viral infection. Specifically, we aimed to investigate whether there was a correlation between Mobility Trends and the spread of Covid-19 virus. Thus, in the conclusion it should be noted that the intensity of pedestrians, traffic and transit traffic during the study period, on average, after 15-20 days, affected the spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…Even after this date, the Rt value was very close to 1, yet it was above this threshold in some moments. This result is like the 21 days found by [25] and the 15-20 days found by [26]. It is noteworthy that these studies use different methodologies to the current study, and a direct comparison would not be entirely adequate.…”
Section: Discussionsupporting
confidence: 54%
“…Even after this date, the Rt value was very close to 1, yet it was above this threshold in some moments. This result is like the 21 days found by [25] and the 15-20 days found by [26]. It is noteworthy that these studies use different methodologies to the current study, and a direct comparison would not be entirely adequate.…”
Section: Discussionsupporting
confidence: 54%
“…Travel quarantine delayed epidemic progression there by 3–5 days ( Chinazzi et al, 2020 ). Gondauri and Batiashvili (2020) , analyzing the mobility in nine countries, found that trips performed one day are directly related to COVID-19 cases after 15–20 days. According to Cot et al (2021) , this lag period is two to five weeks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Di antara kebijakan tersebut adalah social distancing atau Pembatasan Sosial Berskala Besar (PSBB), work from home dan school from home. Kebijakan-kebijakan tersebut bertujuan untuk menekan mobilitas penduduk untuk meminimalkan pertambahan jumlah kasus harian COVID-19 sebagaimana kesimpulan sementara pada kebijakan serupa di beberapa negara lain di dunia (Badr, 2020;Buckee, 2020;Gondauri, 2020;Wilson, 2020).…”
Section: Pendahuluanunclassified